Does ESG really matter to the bank's stability in ASEAN countries? - Huong Lan Do; Hong Hai Ho; The Cuong Mai; Thu Nga Nguyen; Thai Son Nguyen (Cogent Economics & Finance, 2024)
On the rising interest in the sustainability and stability of commercial banks in ASEAN, we set out to examine the impacts of Environmental, Social, and Governance (ESG) activities on bank stability in this region. We build models based on signal theory, stakeholder theory, and overinvestment theory. Upon data collected from banks in the ASEAN from 2015 to 2022, we perform various econometric analyses, including system GMM (Generalized Method of Moments), to demonstrate that attending to ESG imposes an inverse effect on bank stability. It can be seen that the implementation of ESG in banks in ASEAN countries is at the expense of current sustainability. However, in the future, this relationship may be different. The findings support several implications for research and practice in the ASEAN banking environment. While vast evidence has been accumulated in developed countries on the positive contribution of ESG to the stability of the bank, little is found in developing countries. We find significant evidence to support that banks in developing countries should be cautious with spending on ESG activities since it consistently and significantly suppresses the overall stability of the bank.
Keywords: 330; Adverse effects of ESG; Asian Economics; Bank stability; CSR in emerging market; ESG in ASEAN